Compassion Fatigue in Informal Caregivers of Children with Cancer; a Section from Turkey. Issue 8 (17th November 2022) - Orbay, İsmail; Baydur, Hakan; Uçan, Gülten
ABSTRACT: Compassion fatigue is the natural stress caused by the strong desire to help a valued person and alleviate the pain he/she suffers after he/she undergoes a traumatizing event. That caregiver who witnesses the physical suffering of the patient, who makes intense effort during the process deprived of the social, psychological, or economic support they need is among the reasons causing compassion fatigue. In this study, the aim was to test and describe the effects of compassion fatigue on informal caregivers of children with cancer. The study is phenomenological, a form of a qualitative study. The participants were the relatives of children with cancer. The data were obtained through in-depth interviews. The audio-recorded interviews were analyzed through the inductive thematic analysis to obtain answers to the questions. The findings were categorized under four headings which compassion fatigue was addressed: Empathy ability, compassion stress, problems experienced by the participants as components of compassion fatigue. The results of this study demonstrated that mothers were at risk of compassion fatigue. Those who give care to their relatives are faced with problems more than professionals. It is recommended that the implementation of multidisciplinary interventions that will improve caregivers' well-being, and preventive social work interventions, will prevent them from compassion fatigue.